2007
DOI: 10.1097/sla.0b013e318155a9c7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Micrometastases in Colon Cancer

Abstract: This is the first prospective evaluation of the prognostic impact of MM in colorectal cancer. These results indicate that the detection of MM may be clinically relevant in CC and may improve the selection of patients for adjuvant systemic chemotherapy. Patients with CC who are node negative by cumulative detection methods (H&E/IHC and qRT) are likely to be cured by surgery alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…Two hundred fifty-three patients provided written informed consent and were enrolled over a 6-year study period in two prospective multi-center clinical trials of LN ultra-staging in CRC 12, 17. Eligibility criteria have been previously described 12, 17.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two hundred fifty-three patients provided written informed consent and were enrolled over a 6-year study period in two prospective multi-center clinical trials of LN ultra-staging in CRC 12, 17. Eligibility criteria have been previously described 12, 17.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria have been previously described 12, 17. In brief, study subjects were adults (18 years of age or older) with potentially curable primary non-metastatic colon (n=217) or rectal (n=36) carcinoma detected by endoscopy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently reported interim results regarding the prognostic impact of micrometastases, and a mean follow-up of 25 months in 152 CRC patients found no recurrences in patients deemed nodenegative after SLNB by H&E, IHC, and RT-PCR compared with six recurrences in patients who were tumor-node-positive according to IHC or RT-PCR staining. 43 Lim et al found equivalent outcomes in patients with SNs positive by IHC only compared with those who were truly node-negative. 42 Additional issues regarding SLNB in CRC patients include the need for considerable surgeon experience, a variable false-negative rate with frequently aberrant lymphatic anatomy, and the marginal results achieved in patients with rectal cancer.…”
Section: Colon Cancermentioning
confidence: 99%